Analyzing Level of International Humanitarian Law Knowledge and its Compliance Through Military Simulation Game - William Hokianto; Melissa Indah Fianty (ULTIMATICS, 2022)
International humanitarian law in armed conflicts, the majority of whose contents originate from the results of the Geneva Convention, is the law used to protect human rights during an armed conflict. Based on research conducted by the International Red Cross Committee, video games that are now popular among the public, especially in the military genre, often ignore or contradict aspects of international law. This research was conducted to determine the knowledge of international law in armed conflict and its relationship to the level of compliance through military simulation video game scenarios. The scenario-based framework is a method used to develop game scenarios. The scenario was developed using an ARMA 3 video game editor and created to describe a situation of armed conflict where the respondent will take action whose results reflect the respondent's level of compliance with international law. Each respondent obtained two types of scores, the first is knowledge scores obtained from filling out questionnaires, and the second is compliance scores obtained from the results of running scenarios in the game. The score is divided into 12 parameters relating to aspects of international law in armed conflict. After the two types of scores are obtained, an analysis is carried out to determine whether the respondent's knowledge level influences the compliance level. The study's results showed that the respondent's knowledge and compliance levels were very high. The results of the comparative analysis show that only ten parameters have a level of knowledge that influences the level of compliance.